1995
DOI: 10.1002/ijc.2910630507
|View full text |Cite
|
Sign up to set email alerts
|

Presence and persistence of HPV infection and p53 mutation in cancer of the cervix uteri and the vulva

Abstract: We studied 51 cervical carcinomas, among them 25 squamous-cell carcinomas (SCC) and 26 cervical adenocarcinomas (AdCa), and 40 vulvar SCC for the presence of HPV and mutant p53. HPV was detected by PCR, and p53 alterations by temperature-gradient gel electrophoresis/direct sequencing and immunohistochemistry. HPV, mostly type 16/18, was found in 80.4% of the cervical tumors (92.0% of the SCC and 69.2% of the AdCa), but in only 27.5% of vulvar carcinomas. In contrast, p53 mutations were found in 7.8% and 52.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
42
3
6

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 19 publications
9
42
3
6
Order By: Relevance
“…This has suggested the possibility that a viral agent such as BK virus (BKV), which infects the urinary tract and encodes tumor antigens that inactivate these tumor suppressors, may play a role in the etiology of prostate cancer. This would be very similar to the way in which the E6 and E7 oncogene products of human papillomavirus (HPV) inactivate p53 and pRB, respectively, in cervical carcinomas (13,22,27,37,49,72,73). It has been suggested that exposure to infectious agents can cause injury to the normal prostate epithelium, leading to the development of PIA (reviewed in reference 20).…”
mentioning
confidence: 81%
“…This has suggested the possibility that a viral agent such as BK virus (BKV), which infects the urinary tract and encodes tumor antigens that inactivate these tumor suppressors, may play a role in the etiology of prostate cancer. This would be very similar to the way in which the E6 and E7 oncogene products of human papillomavirus (HPV) inactivate p53 and pRB, respectively, in cervical carcinomas (13,22,27,37,49,72,73). It has been suggested that exposure to infectious agents can cause injury to the normal prostate epithelium, leading to the development of PIA (reviewed in reference 20).…”
mentioning
confidence: 81%
“…Recently, p53 mutation frequency in vulvar carcinomas is reported to be much higher compared with cervical carcinoma by 24%, (Lee et al, 1994), 53% (Milde-Langosch et al, 1995) and Elderly Japanese women with cervical carcinoma show higher proportions of both intermediate-risk human papillomavirus types and p53 mutations 53% (Kagie et al, 1997). Vulvar cancer generally occurs in women over ten years older than women with cervical cancer, with a peak incidence between 65 and 75 years old (Langosch et al, 1995).…”
mentioning
confidence: 99%
“…Vulvar cancer generally occurs in women over ten years older than women with cervical cancer, with a peak incidence between 65 and 75 years old (Langosch et al, 1995). The incidence of high-risk HPVs, such as types 16 and 18, is lower in vulvar cancers than in cervical cancers (Nagano et al, 1996), the finding suggesting that mutation of p53 together with HPV may be involved in the carcinogenesis of the vulva.…”
mentioning
confidence: 99%
“…2,9,10 Inconsistencies in p53 positivity rates in cervical as opposed to head and neck cancers can be explained by differences in the rates of p53 mutation. p53 mutations have rarely been detected in HPV-positive cervical cancers 11 but appear to coexist with HPV in some head and neck cancers. 12 The detection of p53 protein in cervical cancers by immunohistochemistry has mainly been attributed to the use of antibodies which detect stabilization of wild-type protein resulting from ongoing stress or disruption to proteins involved in p53 degradation, such as MDM2 11 in addition to mutations.…”
mentioning
confidence: 99%